PERAN PENDIDIKAN POLITIK DALAM MEMBANGUN SIKAP DEMOKRATIS SISWA MELALUI ORGANISASI SISWA INTRA SEKOLAH DI SMP NEGERI 22 SEMARANG - Shalihudin, Farid; Hermanto, Fredy (Sosiolium : Jurnal Pembelajaran IPS, 2021)
This study aims to determine the school's efforts in building student democratic attitudes through OSIS at SMP Negeri 22 Semarang. The results showed that schools made an effort to provide an understanding of political education. The OSIS management has implemented the understanding of political education provided by the school and can be seen through its activities. The implementation of understanding political education in building democratic attitudes is still not optimal. The active participation of the OSIS management includes; (1) decision making, (2) implementation, (3) taking benefits, (4) evaluation, and (5) social attitudes. Meanwhile, the results of the analysis of the role of political education in building student democratic attitudes show that coaching seeks to build the awareness of the student council officials, motivation plays a role in problem solving, and evaluation plays a role in knowing the shortcomings of the student council administrators. Penelitian ini bertujuan untuk mengetahui upaya sekolah dalam membangun sikap demokratis siswa melalui OSIS di SMP Negeri 22 Semarang. Hasil penelitian menunjukkan bahwa sekolah berupaya dalam memberikan pemahaman pendidikan politik. Pengurus OSIS sudah mengimplementasikan pemahaman pendidikan politik yang diberikan sekolah serta dapat diketahui melalui aktivitasnya. Implementasi pemahaman pendidikan politik dalam membangun sikap demokratis masih ada yang belum maksimal. Partisipasi aktif pengurus OSIS meliputi; (1) pengambilan keputusan, (2) pelaksanaan, (3) pengambilan manfaat, (4) evaluasi, dan (5) sikap sosial. Sedangkan hasil analisis peran pendidikan politik dalam membangun sikap demokratis siswa menunjukkan bahwa pembinaan berupaya dalam pembentukan kesadaran pengurus OSIS, motivasi berperan dalam penyelesaian masalah, dan evaluasi berperan dalam mengetahui kekurangan pengurus OSIS.